Interleukin‐33 is a Novel Immunosuppressor that Protects Cancer Cells from TIL Killing by a Macrophage‐Mediated Shedding Mechanism (Adv. Sci. 21/2021). Issue 21 (3rd November 2021) - Wu, Jing; Chen, Ziqing; Wickström, Stina L.; Gao, Juan; He, Xingkang; Jing, Xu; Wu, Jieyu; Du, Qiqiao; Yang, Muyi; Chen, Yi; Zhang, Dingding; Yin, Xin; et al.
Abstract : Cancer Cells In article number 2101029 by Yihai Cao and co‐workers, it is shown that interleukin‐33 (IL‐33)‐activated macrophages protect melanoma cells from tumor‐infiltrating lymphocytemediated killing. This cover shows a new mechanism of immune T cell‐mediated cancer killing. In the tumor environment, macrophages produce proteases to affect the T cell and cancer cell interaction. The monkey king represents immune T cell, and the bull demon represents cancer cell.